(untitled) (Journal of Rangpur Medical College, 2023)
Background: Colorectal cancer is one of the most common causes of death among patients. This study aimed to see the pattern of colorectal cancer from 2018 to 2021 and to explore its association with age and sex, its site of occurrence, histopathological types & its incidence in different regions of the Rangpur division. Methods: This cross-sectional study was carried out in the Department of Radiotherapy, Rangpur Medical College Hospital, Rangpur, Bangladesh. All data regarding 434(7.5%) colo-rectal cancers out of 5782(100%) patients were collected from 2018 to 2021. Each of the 434 colorectal cancer patients was interviewed and examined thoroughly before data collection. Age, sex, previous & current data of all patients were recorded properly during the study. Result: The study showed out of 436 colo-rectal cancers 266(61.3%) were male and 168(38.7%) female with a male-female ratio of 1.58:1. Highest incidence of cancer was in the age group 41-60 years (194,44.7%). Out of 436 cancers 219(50.4%) found in rectum, 29(6.6%) in sigmoid colon and 186(42.8%) in other parts of colon. The most common histopathological type was adenocarcinoma 415(95.62%). Among eight districts of the Rangpur division highest incidence of colorectal cancer was found in Rangpur 194(44.7%) followed by Nilphamari 64(14.7%), Gaibandha 44(10.1%), Kurigragm 40(9.2%), Dinajpur 35(8.06%), Lalmonirhat 34(7.9%), Panchagarh 12(2.7%) and Thakurgaon 11(2.5%). Conclusion: The incidence of colorectal cancer is higher in males than females. Highest incidence of colorectal cancer in the age group of 41-60 years. Adenocarcinoma is the most common histopathological type of colorectal cancer in both males and females. Incidence of the colo-rectal cancer in the Rangpur district is higher than in other districts of Rangpur division. J Rang Med Col. September 2023; Vol. 8, No. 2: 44-47